Tailored polyimide as positive electrode and polyimide-derived carbon as negative electrode for sodium ion full batteries. Issue 7 (12th February 2020) - Wang, Cunguo; Chu, Rongrong; Guan, Zhixing; Ullah, Zaka; Song, Hewei; Zhang, Yingfei; Yu, Congcong; Zhao, Liyi; Li, Qi; Liu, Liwei
Abstract : Organic electrode materials have secured a distinctive place among the auspicious choices for modern energy storage systems due to their resource sustainability and environmental friendliness. Abstract : Organic electrode materials have secured a distinctive place among the auspicious choices for modern energy storage systems due to their resource sustainability and environmental friendliness. Herein, a novel all-organic electrode-based sodium ion full battery is demonstrated using 1, 4, 5, 8-naphthalenetetracarboxylic dianhydride (NTCDA) as raw material for the assembly of positive and negative electrodes. Both the electrodes exhibit excellent cycling stability and rate performance. The fabricated organic sodium ion full battery not only displays a high initial capacity of 157 mA h g −1 with an average battery voltage of 1.47 V under the current density of 100 mA g −1, but also delivers a high energy density of 254 W h kg −1 and a high power density of 614 W kg −1 . These sodium ion batteries with organic positive and negative electrode materials can provide a new way for energy storage devices.